Fast response electrochemical capacitor electrodes created by laser-reduction of carbon nanodots. (March 2019) - Strauss, Volker; Anderson, Mackenzie; Turner, Christopher L.; Kaner, Richard B.
Abstract: The conversion of small bio-based molecules into electro-active functional carbon nanomaterials such as carbon nanodots or graphene is attracting increasing interest. In this communication we demonstrate the use of laser-reduced carbon nanodots (lrCND) as electrodes for electrochemical capacitors. A CO2 -laser-assisted process is utilized to convert CNDs into highly conductive 3D-carbon monoliths. Exclusion of molecular oxygen from the reaction environment has a positive effect on device parameters and particularly on the frequency response. Using this simple and inexpensive method, an extremely fast RC time constant of 0.29 ms and a capacitance of 0.259 mF cm −2 at 120 Hz were obtained. This can be attributed to an effective conversion of CNDs into graphitic carbon in an oxygen-free environment and the presence of unconverted CNDs in the 3D-carbon network acting as doping agents. Graphical abstract: Image 1 Highlights: Bio-molecule based carbon nanodots were converted into 3D-carbon. The role of molecular oxygen in the reaction environment was investigated. High-frequency electric double layer capacitors were fabricated. RC time constant of 0.29 ms and a capacitance of 0.259 mF cm −2 at 120 Hz were obtained.